The Hubungan Self Care Dengan Kualitas Hidup Pasien Diabetes Mellitus Di Puskesmas Guntung Payung Kota Banjarbaru - Lestari, Agustina; Hamba, Ria Anggara; Saputra, Adisurya; Rahayu, Septian Mugi; Rahmah, Puja Sagita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: To determine the relationship between Self Care and the Quality of Life of Diabetes Mellitus (DM) patients at the Guntung Payung Health Center, Banjarbaru City, South Kalimantan Province Methods: This research is a quantitative study with a cross-sectional study design, the samples taken were 37 respondents. The sampling technique uses Total Sampling. Results: from the bivariate analysis showed that there was a relationship between Self Care and the Quality of Life of Diabetes Mellitus (DM) patients with statistical test results using a Chi-Square p value of 0.000. . Conclusion: That there is a relationship between Self Care and the Quality of Life of Diabetes Mellitus (DM) patients at the Guntung Payung Health Center, Banjarbaru City, South Kalimantan Province